2021
DOI: 10.22271/oral.2021.v7.i4e.1391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of shear bond strength of all surface bonding primer with a conventional primer using two different materials of brackets bonded to different surfaces: An in vitro study

Abstract: Orthodontic treatment frequently requires bonding brackets onto various types of surfaces like enamel, metal restorations, composites, ceramics, zirconia, acrylic temporaries etc. The development of new materials and techniques, simplifies the clinical procedures. The purpose of the present study was to evaluate the SBS of all surface bonding Primer (Assure plus Primer) compared with conventional primer (Transbond XT) onto tooth, acrylic temporary crown and Zirconia crown surfaces using metal and ceramic brack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The previous results were also confirmed by Wang et al (8) who reported a SBS of 10.98 MPa with a similar protocol, the thermocycling in this study was 500 cycles. Jamal et al (37) evaluated the effectiveness of RA plus in bonding ceramic brackets to feldspathic porcelain. The samples were roughened by a diamond bur, silane was applied followed by RA plus.…”
Section: Discussionmentioning
confidence: 99%
“…The previous results were also confirmed by Wang et al (8) who reported a SBS of 10.98 MPa with a similar protocol, the thermocycling in this study was 500 cycles. Jamal et al (37) evaluated the effectiveness of RA plus in bonding ceramic brackets to feldspathic porcelain. The samples were roughened by a diamond bur, silane was applied followed by RA plus.…”
Section: Discussionmentioning
confidence: 99%